Classicism in South Africa - Dominik, William J. (2021)
This exceptional volume edited by Grant Parker on the role of Classics and its heritage in South Africa has been in preparation for a number of years. Whatever time was necessary to produce South Africa, Greece, Rome: Classical Confrontations has shown to be well worth the wait for scholars of the classical reception and tradition.1 Parker declares that the aims of his edited volume are to examine South Africa’s past in relation to classical antiquity (p. xxi), to extract specifically South African contexts of this antiquity, and to examine the ‘afterlives’ of classical culture in the country (p. 6).